Hemophagocytic lymphohistiocytosis: an unusual complication in Orientia tsutsugamushi disease (scrub typhus). - Aneesh Basheer; Somanath Padhi; Vinoth Boopathy; Saumyaranjan Mallick; Shashikala Nair; Renu G'Boy Varghese; Reba Kanungo (Mediterranean Journal of Hematology and Infectious Diseases)
Background: Hemophagocytic lymphohistiocytosis (HLH) is an uncommon, potentially fatal, hyperinflammatory syndrome that may rarely complicate the clinical course of Orientia tsutsugamushi disease (scrub typhus). Methods: We describe here the clinicopathological features, laboratory parameters, management, and outcome data of three adult patients (1 female, 2 males) with scrub typhus associated HLH from a tertiary center with a brief and concise review of international literature. Results: All three patients satisfied the HLH-2004 diagnostic criteria; one had multi organ dysfunction with “sky high” ferritin level; and all had a dramatic recovery following doxycyclin therapy. Literature review from January 1990 to March 2014 revealed that scrub typhus associated HLH were reported in 21 patients, mostly from the scrub endemic countries of the world. These included 11 females and 10 males with mean age of 35 years (range; 8 months to 81 years). Fifteen of 17 patients (where data was available) had a favorable outcome following early serological diagnosis and initiation of definitive antibiotic therapy with (N=6) or without (N=9) immunosuppressive/immunomodulator therapy. Mutation analysis for primary HLH was performed in one patient only, and HLH-2004 protocol was used in two patients. Conclusion: We suggest that HLH should be considered in severe cases of scrub typhus especially if associated with cytopenia (s), liver dysfunction, and coagulation abnormalities.  Further studies are required to understand whether an immunosuppressive and/or immunomodulator therapy could be beneficial in those patients who remain unresponsive to definitive antibiotic therapy.